British Jobs for British Workers? Negotiating Work, Nation, and Globalisation through the Lindsey Oil Refinery Disputes. Issue 1 (28th May 2014) - Ince, Anthony; Featherstone, David; Cumbers, Andrew; MacKinnon, Danny; Strauss, Kendra
Abstract This paper explores the relationships between labour organising, globalisation and national identity through an engagement with the 2009 Lindsey Oil Refinery strikes. Some strikers adopted the controversial slogan 'British Jobs for British Workers' in response to employers' attempts to undercut existing wages and conditions with a new migrant workforce. This led to accusations of xenophobia. We make three inter‐related arguments. First, we contend that it is necessary to interrogate the spatialised power relations generated through particular forms of labour agency enacted in relation to globalising processes. Second, since these responses can be politically ambiguous, success in territorially based disputes does not always equate with broader (transnational) class agency. Third, relevant to the project of labour geography, we propose that labour scholars and activists be more attuned to the mundane ambiguities in labour agency, and the subsequent need to frame local action within a broader relational politics of global labour solidarity.